Debating Lebanon's Power-Sharing Model - Fakhoury, Tamirace (2014)
The terms power sharing, consociational democracy, and consociationalism10 are used inter- changeably in consociational literature to categorize the Lebanese situation. [...]alternative expressions such as "political pluralism," "political confessionalism," or "political sectarianism"11 offer scholars whose primary research focuses on Lebanon heuristic tools with which to describe how the consociational method has been reappropriated in the Lebanese case. According to one dominant perspective, Lebanese sectarian communities are the "boundary markers" in Lebanon's "social stratifica- tion"13 as well as the building blocks structuring political relations.